Pengaruh Kualitas Pelayanan Dan Manajemen Pengelolaan Badan Amil Zakat Nasional Kabupaten Bekasi Terhadap Kepuasan Masyarakat - Andi Suhandi; Azmy MH; Bayu Umara; Bernad Hananto; Rahmayani Desvita (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2024)
This study aims to examine how much influence the quality of service and management at BAZNAS Bekasi Regency has on community satisfaction. This study uses the independent variable, namely the quality of service and management and the dependent variable is community satisfaction.  And the sample of this research is the residents of Cibatu Village, South Cikarang District. The analytical technique used is validity test and reliability test, then classic assumption test and hypothesis test, namely t test, f test, determination test, using and processed by SPSS 24. The results of this study state that partially the quality of service affects people's satisfaction at the National Amil Zakat Agency of Bekasi Regency. And simultaneously the quality of service and management have a significant effect on community satisfaction at the National Amil Zakat Agency of Bekasi Regency by 82.9%.